Factors associated with the proportion of abnormal results in screening mammograms: ecological study - Tatiana do Valle Lovato Sverzut; Inara Pereira da Cunha; Karine Laura Cortellazi; Gláucia Maria Bovi Ambrosano; Vanessa Gallego Arias Pecorari (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the factors associated with the proportion of abnormal results in screening mammograms. Methods: Ecological study, with data from DATASUS/SISCAN, Atlas Brasil do Desenvolvimento Humano, Fundação SEADE, and Sistema e-Gestor, from 2016 to 2019, of women aged 50 to 69 years in the 645 municipalities of São Paulo (Brazil). Independent variables were associated with the outcome: proportion of unsatisfactory coverage of abnormal test results (Breast Imaging Reporting and Data System - BI-RADS® 0, 4 and 5 proportion >10% of tests performed). Multiple Poisson regression was used. Results: Higher proportion of screening mammography (PR=1.20; 95%CI: 1.00;1.45), higher percentage of poor (PR=1.20; 95%CI: 1.07;1.36), low (PR=1.57; 95%CI: 1.38;1.78) and medium coverage of the Family Health Strategy (ESF) (PR=1.30; 95%CI: 1.09;1.52) were associated to the outcome. Conclusion: Socioeconomic and FHS coverage factors mediate the proportion of mammograms with abnormal results in public health services. Therefore, they are important aspects in the fight against breast cancer.